The evolution of Oppel's 'Macrocephalusbett' (Callovian, Middle Jurassic). (16th May 2017) - Mönnig, Eckhard
Abstract : In his basic work of 1856–1858, Albert Oppel subdivided his 'Juraformation' into eight stages and 32 zones. There is a long history of confusion as to the meaning of Oppel's zones. Using his 'Macrocephalusbett' and his 'Zone des Amm. macrocephalus ', it is explained how his concept has been developed until today. Both and also Oppel's 'Macrocephalus Schichten' are chronostratigraphical units and correspond to today's Lower Callovian. The Lower Callovian was first subdivided by Buckman and Spath into three zones: Herveyi, Koenigi and Calloviense. These units hold good for the Subboreal Province in Central Europe and England and became the primary standard. In addition, there are four more secondary standard zonations in other faunal provinces. In terms of the ammonites, the amount and quality of material available improved and also the methods used to assess morphological similarities. That makes a finer resolution possible, and today, the Lower Callovian of England and Central Europe consists of eight subzones with about 20 biohorizons.